Cotton wool in a cup: regarding one expression from the story by Agatha Christie - Bogatyrev Arseniy Vladimirovich (Studia Humanitatis)
The paper studies a remarkable humorous saying “Moorish” found in the work by Agatha Christie. The author tries to discover the origins of the analysed phrase by comparing Russian translation with the English original. Having focused in detail on the semantics of the lexeme “Moorish”, the author draws on a variety of material, including geographical and historical properties. The author makes an attempt to find out the reason for the writer’s use of this expression, to trace the connection of the saying with the inner world of the author. In conclusion, the importance of Miss Marple’s recollection of one joke of her uncle Henry for understanding the meaning of the entire work of Agatha Christie is highlighted.